Founder events influence structures of Aspergillus flavus populations - Ortega‐Beltran, A.; Callicott, K.A.; Cotty, P.J. (Wiley, 2020)
In warm regions, agricultural fields are occupied by complex Aspergillus flavus communities composed of isolates in many vegetative compatibility groups (VCGs) with varying abilities to produce highly toxic, carcinogenic aflatoxins. Aflatoxin contamination is reduced with biocontrol products that enable atoxigenic isolates from atoxigenic VCGs to dominate the population. Shifts in VCG frequencies similar to those caused by the introduction of biocontrol isolates were detected in Sonora, Mexico, where biocontrol is not currently practiced. The shifts were attributed to founder events. Although VCGs reproduce clonally, significant diversity exists within VCGs. Simple sequence repeat (SSR) fingerprinting revealed that increased frequencies of VCG YV150 involved a single haplotype. This is consistent with a founder event. Additionally, great diversity was detected among 82 YV150 isolates collected over 20 years across Mexico and the United States. Thirty‐six YV150 haplotypes were separated into two populations by Structure and SplitsTree analyses. Sixty‐five percent of isolates had MAT1‐1 and belonged to one population. The remaining had MAT1‐2 and belonged to the second population. SSR alleles varied within populations, but recombination between populations was not detected despite co‐occurrence at some locations. Results suggest that YV150 isolates with opposite mating‐type have either strongly restrained or lost sexual reproduction among themselves.